Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.
Let W = {(f(x)∈ P2[R] : f '(x) + xf(0) = 0}

i) Prove that W is a subspace of P2[R].

ii) Find a basis for W.

Here's what I have so far:

i) I have to verify that the subspace (1) contains the zero space, (2) is closed under addition, and (3) is closed under scalar multiplication.

i) 
    (1) Contains the zero space
        f'(x) + xf(0) = 0
        f'(0) + (0)f(0) = 0
        0 = 0, 
        so 0 ∈ W

I'm stuck on numbers 2 and 3, because I'm not sure how to represent f '(x) + xf(0) = 0 with examples that I can just plug in and show that it is closed under addition and scalar multiplication.

I generally do these problems with vectors or the like - for example, if the question was

Let Let W = {(x, y, z)∈ R^3 : x + y - 2z = 0}

and I wanted to show if it was a subspace, I would just show from some vectors v1 = (a1, a2, a3) and v2 = (b1, b2, b3) that

(a1 + b1) + (a2 + b2) - 2(a3 + b3) = (a1 + a2 - 2a3) + (b1 + b2 - 2b3), thus is closed under addition

and

c(a1 + a2 - 2a3) = ca1 + ca2 - 3ca3, thus is closed under scalar multiplication.

and I would find the basis by just finding the kernel of x + y - 2z = 0

I'm not sure how to deal with the problem when it is converted into polynomials. Thanks.

share|improve this question
1  
You don't need to check that the point $0$ is in this set. You need to check the function $(x\mapsto 0)$ is in this set (that's the zero vector in this vector space). –  Bryan Jul 21 at 3:51
    
Keep in mind that the 'basis vectors' of a polynomial ring are the monomials $1,x,x^2,\ldots$ themselves. So you could just as well write a polynomial $1+3x-x^2$ as the vector $(1,3,-2)$. –  Semiclassical Jul 21 at 3:52
    
Wait, because verified that the POINT 0 is in the set instead of the vector 0 is in the set, did I do the first step incorrectly? –  Theo Jul 21 at 4:12
    
Yeah, actually your proof of (1) needs revising. You don't replace $x$ by 0. You replace $f$ by the function $0$, and the desired equality follows for every $x$. –  Silvio Levy Jul 21 at 5:47

2 Answers 2

up vote 1 down vote accepted

Proving (2) goes like this: Suppose that $f$ and $g$ both belong to $W$. Ask yourself why $f+g$ also belongs to $W$. It's easy if you write out the equation that $f$ satisfies, namely $f'(x)+x f(0)=0$, then the equation that $g$ satisfies (same equation, with $f$ replaced by $g$) and then add the two equations and apply the distributive property to get stuff times $(f+g)$.

You will need to use the fact that $(f+g)(x)=f(x)+g(x)$, which is the definition of the sum of two functions, and also the fact that $f'+g'=(f+g)'$, which is an elementary property of the derivative.

Proving (3) is even easier.

share|improve this answer
    
What I did, which I'm not sure is correct, is h, g ∈ W h'(x) + x h(0) = 0 g'(x) + x g(0) = 0 h'(x) + g'(x) + xh(0) + xg(0) = (h'(x) + xh(0)) + (g'(x) + xg(0)), c(g'(x) + xg(0)) = cg'(x) + xg(0) –  Theo Jul 21 at 4:09
    
That's basically right except that you should justify the steps ($h'(x) + x h(0) = 0$ is an assumption, etc.) and you also need to clinch the argument: you've written down $$h'(x) + g'(x) + xh(0) + xg(0) = (h'(x) + xh(0)) + (g'(x) + xg(0)),$$ but the important thing is that this shows that $(h+g)'(x)+x(h+g)(0)=0$, and therefore $(h+g)$ satisfies condition (2). –  Silvio Levy Jul 21 at 4:58
    
I think I got it now for the proof part. Thank you! –  Theo Jul 21 at 5:31

Let $\phi: P_2 \to P_2$, be given by $\phi(p)(t) = p'(t)+t p(0)$. It is easy to verify that $\phi$ is linear.

Then $W = \ker \phi$. Since the null space of a linear operator is a subspace, it follows that $W$ is a subspace.

If we use the basis $\{t \mapsto 1, t \mapsto t, t \mapsto t^2 \}$ for $P_2$, we see that $\phi$ has the matrix representation $\Phi (p_0,p_1,p_2)^T = (p_1, 2p_2+p_0,0)^T$. That is, $\Phi = \begin{bmatrix} 0 & 1 & 0 \\ 1 & 0 & 2 \\ 0 & 0 & 0\end{bmatrix}$. It is straightforward to see that $\dim {\cal R} \Phi = 2$, hence $\dim \ker \Phi = 1$. It is also straightforward to see that $\Phi(2, 0, -1)^T = 0$, hence $\ker \Phi = \operatorname{sp} \{ (2, 0, -1)^T \}$.

Now use the basis above to find a basis for $W$.

share|improve this answer
    
I'm not sure how to arrived here: If we use the basis $\{t \mapsto 1, t \mapsto t, t \mapsto t^2 \}$ for $P_2$, we see that $\phi$ has the matrix representation $\Phi (p_0,p_1,p_2)^T = (p_1, 2p_2+p_0,0)^T$. –  Theo Jul 21 at 4:14
    
Suppose $p \in P_2$, then $p(t) = p_0+p_1 t + p_2 t^2$, and so $p'(t)+tp(0) = p_1+(p_0+2 p_2)t$. The representation of $p$ in the basis is $(p_0,p_1,p_2)^T$ and the representation of $t \mapsto p'(t)+tp(0)$ is $(p_1, p_0+2 p_2, 0)^T$. –  copper.hat Jul 21 at 5:40

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.